(untitled) (Global Journal of Human-Social Science, 2012)
This study sets out to examine the relationship between level of poverty and vulnerability to attack of HIV AIDS It attempted to analyse the probability of attack of AIDS especially among female adolescents if their economic condition of living is poor The study adopted both primary and secondary sources of data Primary data were obtained from interview conducted on few randomly selected 100 patients of the People Living With HIV AIDS in Ilesa Osun State South Western Nigeria while the secondary data were gathered through journal articles government documents library internet and daily news papers The findings of the study revealed that there is a positive relationship between level of poverty and infection of HIV AIDS especially among female adolescents It further revealed that the poor female adolescents are more susceptible to attack of HIV AIDS infection than those coming from the rich family background This assertion was confirmed by 70 percent of our respondents The paper concluded that there is a strong relationship between poverty among female adolescents and tendency to be vulnerable to HIV AIDS attack